Astrocytoma Mimicking Herpetic Meningoencephalitis: The Role of Non-Invasive Multimodal Monitoring in Neurointensivism - Uri Adrian Prync Flato; Barbara Cristina de Abreu Pereira; Fernando Alvares Costa; Marcos Cairo Vilela; Gustavo Frigieri; Nilton José Fernandes Cavalcante; Samantha Longhi Simões de Almeida (MDPI AG, 2023)
Neuromonitoring is a critical tool for emergency rooms and intensive care units to promptly identify and treat brain injuries. The case report of a patient with status epilepticus necessitating orotracheal intubation and intravenous lorazepam administration is presented. A pattern of epileptiform activity was detected in the left temporal region, and intravenous Acyclovir was administered based on the diagnostic hypothesis of herpetic meningoencephalitis. The neurointensivist opted for multimodal non-invasive bedside neuromonitoring due to the complexity of the patient's condition. A Brain4care (B4C) non-invasive intracranial compliance monitor was utilized alongside the assessment of an optic nerve sheath diameter (ONSD) and transcranial Doppler (TCD). Based on the collected data, a diagnosis of intracranial hypertension (ICH) was made and a treatment plan was developed. After the neurosurgery team's evaluation, a stereotaxic biopsy of the temporal lesion revealed a grade 2 diffuse astrocytoma, and an urgent total resection was performed. Research suggests that monitoring patients in a dedicated neurologic intensive care unit (Neuro ICU) can lead to improved outcomes and shorter hospital stays. In addition to being useful for patients with a primary brain injury, neuromonitoring may also be advantageous for those at risk of cerebral hemodynamic impairment. Lastly, it is essential to note that neuromonitoring technologies are non-invasive, less expensive, safe, and bedside-accessible approaches with significant diagnostic and monitoring potential for patients at risk of brain abnormalities. Multimodal neuromonitoring is a vital tool in critical care units for the identification and management of acute brain trauma as well as for patients at risk of cerebral hemodynamic impairment.